2011
DOI: 10.1016/j.brainres.2011.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Neural generators underlying concurrent sound segregation

Abstract: Although an object-based account of auditory attention has become an increasingly popular model for understanding how temporally overlapping sounds are segregated, relatively little is known about the cortical circuit that supports such ability. In the present study, we applied a beamformer spatial filter to magnetoencephalography (MEG) data recorded during an auditory paradigm that used inharmonicity to promote the formation of multiple auditory objects. Using this unconstrained, data-driven approach, the evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…8 B ). In addition, there are other possible candidates of the neural correlates of auditory streaming, such as auditory mismatch negativity [75][77], object-related negativity [77], [78], stimulus-specific, multiple-time-scale adaptations [79], and stimulus-induced but non-stimulus-locked concerted activities by neuronal ensemble across auditory cortical fields [80], [81]. Furthermore, interactions between cortical and subcortical activities via cortico-fugal connections should be also taken into account [29].…”
Section: Discussionmentioning
confidence: 99%
“…8 B ). In addition, there are other possible candidates of the neural correlates of auditory streaming, such as auditory mismatch negativity [75][77], object-related negativity [77], [78], stimulus-specific, multiple-time-scale adaptations [79], and stimulus-induced but non-stimulus-locked concerted activities by neuronal ensemble across auditory cortical fields [80], [81]. Furthermore, interactions between cortical and subcortical activities via cortico-fugal connections should be also taken into account [29].…”
Section: Discussionmentioning
confidence: 99%
“…This time/energy dependent activity suggests that N1 activity is related with the detection and orientation to changes in the auditory environment. This is corroborated by the fact that it is possible to elicit N1-like responses using both the onset and the offset of a given auditory stimulus (Arnott et al, 2011;Hari et al, 1987). At the neuroanatomical level, the N1 was suggested to be a composite wave reflecting the summation of at least three distinct underlying components (McCallum and Curry, 1980;Näätänen and Picton, 1987).…”
Section: Introductionmentioning
confidence: 82%
“…The P2 is thought to index some aspects of stimulus classification, reflecting primary processes of attentional allocation, perceptual learning, and even memory (Arnott et al, 2011). It has also been suggested that its fronto-central prominence is related to inhibitory processes for interference caused by irrelevant stimulation (Crowley and Colrain, 2004;Dempster, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to model the N1m wave because it was the largest and most reliable deflection from the AEF elicited by the harmonic complex tones. The analysis was performed on the grand average across stimulus types to enhance signal-to-noise ratio and because the differences in source location between the N1m elicited by tuned and mistuned stimuli were expected to be small (Arnott et al, 2011). Peak amplitude and latency were determined as the largest positivity (P) or negativity (N) in the individual source waveforms during a specific interval.…”
Section: Methodsmentioning
confidence: 99%